2006
DOI: 10.1038/modpathol.3800606
|View full text |Cite
|
Sign up to set email alerts
|

Low sensitivity of histology to predict the presence of microorganisms in suspected aseptic loosening of a joint prosthesis

Abstract: Intraoperative histology has a high specificity and sensitivity when a septic prosthesis loosening is suspected. However, its usefulness to predict the presence of microorganisms when aseptic loosening is suspected is not well defined. Intraoperative histology and cultures from periprosthetic tissue of 61 revision arthroplasties performed owing to suspected aseptic loosening were retrospectively reviewed. Frozen sections were evaluated following Mirra's criteria (adapted by Feldman). Culture was considered pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 18 publications
1
31
1
Order By: Relevance
“…However, when positive results are obtained, the specificities are 97% and 91%, respectively. Therefore a positive culture renders both methods valuable which also is supported by another study [5]. An underestimated and contributing problem is that aspiration of an adequate sample of fluid from the hip after arthroplasty usually is more difficult to achieve than from a surgically treated knee [18,19].…”
Section: Resultsmentioning
confidence: 56%
“…However, when positive results are obtained, the specificities are 97% and 91%, respectively. Therefore a positive culture renders both methods valuable which also is supported by another study [5]. An underestimated and contributing problem is that aspiration of an adequate sample of fluid from the hip after arthroplasty usually is more difficult to achieve than from a surgically treated knee [18,19].…”
Section: Resultsmentioning
confidence: 56%
“…Therefore, the AAOS clinical practice guidelines [5] may need to be revisited to avoid misclassification of PJI as aseptic loosening. Some authors reported that low-grade PJI often are misclassified as aseptic loosening when obvious clinical signs of infection are missing [2,17]. An accurate diagnosis of the reason of prosthesis failure is important, particularly the differentiation between aseptic loosening and PJI, because the treatment differs profoundly between these two clinical entities.…”
Section: Discussionmentioning
confidence: 99%
“…5,12,22,23 False-positive results of histology could be because culture and histological specimens are taken from different areas. 5,12,22 Falsenegative results could be attributed to: (1) low virulent microorganisms like Staphylococcus epidermidis 6,7,22,24,25 or Propionibacterium spp 26,27 that do not stimulate neutrophile infiltration, (2) bacteriological contamination of the specimen obtained for culture 12 or (3) the cut-off point (number of neutrophils per field) to establish the diagnosis of infection. 2,4,5,10,13,[28][29][30] Another possibility for inconsistencies in the histological results could be the type of specimen submitted to the laboratory.…”
mentioning
confidence: 99%
“…The majority of investigators obtain specimens from pseudocapsule, synovial surface, interface membrane and any tissue area suspected of infection. [6][7][8]12,15,16,22 The objective of our study was to study which is the most accurate specimen for histological diagnosis of prosthetic joint infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation